Acute and long-term cannabis use among stimulant users: Results from CTN-0037 Stimulant Reduction Intervention using Dosed Exercise (STRIDE) Randomized Control Trial. (1st July 2019) - Vidot, Denise C.; Rethorst, Chad D.; Carmody, Tom J.; Stoutenberg, Mark; Walker, Robrina; Greer, Tracy L.; Trivedi, Madhukar H.
Highlights: Results are from STRIDE Randomized Control Trial, NIDA CTN Protocol 0037. There was a high prevalence of cannabis use among stimulant users at baseline. No differences in short-term reduction of cannabis use between intervention arms. Long-term reduction of cannabis use in the DEI group compared to the HEI group. Abstract: Aims: The aim of this study was to examine the impact of vigorous intensity, high dose exercise (DEI) on cannabis use among stimulant users compared to a health education intervention (HEI) using data from the Stimulant Reduction Intervention using Dosed Exercise, National Institute of Drug Abuse National Drug Treatment Clinical Trials Network Protocol Number 0037 (STRIDE). Methods: Adults (N = 302) enrolled in the STRIDE randomized clinical trial were randomized to either the DEI or the HEI. Interventions included supervised sessions three times a week during the Acute phase (12 weeks) and once a week during the Follow-up phase (6 months). Cannabis use was measured at each assessment via Timeline Follow Back and urine drug screens. Cannabis use was compared between the groups during the Acute and Follow-up phases using both the intent-to-treat sample and a complier average causal effects (CACE) analysis. Findings: Approximately 43% of the sample reported cannabis use at baseline. The difference in cannabis use between the DEI and HEI groups during the Acute phase was not significant. During the Follow-up phase, the days of cannabis use was significantly lower among those in the DEI group (1.20 days) compared to the HEI group (2.15 days; p = 0.04). Conclusions: For those who adhered to the exercise intervention, vigorous intensity, high dose exercise resulted in less cannabis use. Results suggest that there were no significant short-term differences in cannabis use between the groups. Further study on the long-term impact of exercise as a treatment to reduce cannabis use should be considered.